The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.13189/ujer.2016.041218
|View full text |Cite
|
Sign up to set email alerts
|

The Connection Competencies of Pre-service Mathematics Teachers about Geometric Concepts to Daily-life

Abstract: However, geometry is the area with the most concrete possibility of mathematical topics which contains more abstract concepts, students experience difficulties while understanding. Therefore, the connection of issues with daily life to concrete the subjects and the ability of connecting geometric concepts with daily life of the teachers and pre-service teachers who will teach these subjects become more important. In this study, the geometric concepts of pre-service mathematics teachers along with their ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
0
5
0
8
Order By: Relevance
“…In fact, it is not wrong to state that when we talk about mathematics many people in society have only numbers, shapes and calculations in their mind. It is possible to see similar results even in researches conducted among teachers and teacher candidates (Umay, 2003;Garii & Okumu, 2008;Lee, 2012;Özgen, 2013;Pirasa, 2016). For example, Garii and Okumu (2008) were examined the skills of classroom teachers regarding to recognition of mathematics in everyday life.…”
Section: Research Studies About Real Life Connectionsmentioning
confidence: 70%
“…In fact, it is not wrong to state that when we talk about mathematics many people in society have only numbers, shapes and calculations in their mind. It is possible to see similar results even in researches conducted among teachers and teacher candidates (Umay, 2003;Garii & Okumu, 2008;Lee, 2012;Özgen, 2013;Pirasa, 2016). For example, Garii and Okumu (2008) were examined the skills of classroom teachers regarding to recognition of mathematics in everyday life.…”
Section: Research Studies About Real Life Connectionsmentioning
confidence: 70%
“…The results were however, related to Phillips and Marttinen (2013), Finn and McInnis (2014) and Kokko, Eronen and Sormunen (2015) who found that cross-curricular integration is successful in an array of disciplines. And again confirms, Eli (2009) (as cited by Pirasa, 2016) assertion that the knowledge of pre-service mathematics teachers for geometry instruction was at a low level and that the mathematical connection carried out was a lot more operational rather than being conceptual.…”
Section: Discussionmentioning
confidence: 68%
“…The results obtained do not support the assertion that pre-service teachers are deficient in integrating geometry and soccer. For example, the result obtained does not support the idea of a deficiency in pre-service teachers' content knowledge of geometry and pedagogy in integrating soccer and geometry as suggested by Pirasa, (2016). Ginsburg (2008), examined high school mathematics teachers' abilities of connecting mathematics with daily life, also does not lend support to this finding.…”
Section: Discussionmentioning
confidence: 73%
“…Öğretmen boyutu araştırmaları ile yakın ilişkili olarak, literatür taraması kapsamında üzerinde durulacak üçüncü çalışma teması öğretmen adaylarıyla yapılan araştırmalardır (Gainsburg, 2008;Mandacı Şahin, 2019;Özgeldi ve Osmanoğlu, 2017;Mumcu, 2018;Yorulmaz ve Çokçalışkan, 2017;Pirasa, 2016). Örneğin, Özgeldi ve Osmanoğlu (2017) ortaokul matematik öğretmen adaylarına sundukları kazanımlar ışığında kendilerinden gerçek hayatla ilişkilendirme yapmalarını talep etmişlerdir.…”
Section: Gerçek Hayatla İlişkilendirme Araştırmalarıunclassified
“…Çalışmanın bulguları, öğretmen adaylarının toplumda matematiğin tartışılması için %27, klasik problem için %23, gerçek verinin incelenmesi için %17, matematik kavramaları ve uygulamalı gösterimler için %17, basit analojiler için %10 ve gerçek olayların matematiksel modellenmesi için %6 oranında gerçek hayatla ilişkilendirme yaptıklarını göstermiştir. Pirasa (2016) ilköğretim matematik öğretmen adaylarının geometri kavramlarını derslerde kullanılan klasik terimler aracılığıyla gerçek hayatla ilişkilendirdiklerini, ilkokuldan itibaren öğrenilen günlük hayat durumlarını ilişki kurmak için örnek olarak sunduklarını (ör. kare için fotoğraf çerçevesi), dolayısıyla gerçek hayatla ilişkilendirmelerinin özgünlük barındırmadığını ortaya koymuştur.…”
Section: Gerçek Hayatla İlişkilendirme Araştırmalarıunclassified